Intrinsic and Extrinsic Motivation to Learn as Factors of Resilience in Students' Pedagogical Disciplines - Pilot Study - Dubayová, Tatiana; Haficová, Hedviga (Central European Journal of Educational Research, 2023)
Motivation determines the dynamics of behaviour and helps in overcoming obstacles. A related concept is resilience, which also relates to overcoming stressful situations and speaks to an individual’s ability to adapt to challenging circumstances in life. The aim of this paper was to investigate the relationship between resilience and motivation to learn in students studying in the field of education. One hundred and thirty students participated in the research (100 bachelor students and 30 master students). The research instrument used to measure resilience was The Connor-Davidson Resilience Scale (CD-RISC 10) and to detemine motivation The Academic Motivation Scale (AMS-C 28) tool was used. The Mann-Whitney test found no significant difference between the two groups of students in each of the variables measured. The results show a significant association between resilience and types of intrinsic motivation in particular, but the strongest relationship was found between resilience and the lack of motivation. Students with low resilience scored higher on amotivation. For students at university, motivation to learn based on intrinsic drives is assumed to be self-evident. However, the ability to overcome obstacles is also necessary for the attainment of learning goals. Its degree can also be developed through educational intervention, which provides an opportunity for university teachers to expand their area of operation.